THE KINETIC OF ACTIVATED MONOCYTES IN ACUTE PHASE DENGUE INFECTION - Umi Solekhah Intansari; Arif Bahiyuddin bin Badaruddin; Ida Safitri Laksanawati (Tropical Medicine Journal, 2011)
Introductions: Nowadays dengue infection is at present one of the most common mosquito-borne viral diseases of humans worldwide. Initially, Dengue infections were primarily recorded when they occurred as epidemics in tropical and subtropical countries. Monocyte/macrophage infection is central to the pathogenesis of dengue fever and to the origin of dengue hemorrhagic fever. Increased activation of monocytes and greater numbers of DEN-infected cells were associated with more severe Dengue, implicating a role for monocyte activation in dengue immunopathogenesis. Thus, more knowledge about the relation between numbers of activated monocyte with dengue severities is essential for better understanding regarding this subject.Objectives: Studying the relation between numbers of activated monocyte, marked by HLA-DR marker intensity with Dengue Fever severity throughout the disease course, from day 2 until day 6 of acute dengue fever.Methods: This research is cross sectional observational study. The location in done at Dr. Sardjito Hospital in 6 months time.Results: There is a negative correlation between median number of activated monocyte with dengue severity, on day 3 of acute dengue fever.Conclusion: There was a negative correlation between numbers of activated monocyte marked by HLADR intensity with disease severity on day 3 of acute dengue infection.Keywords: Activated Monocyte; Human Leukocyte Antigen (HLA)-DR intensity; Percentage of Activated Monocyte; Dengue Fever Severity.